Promoting Religious Tolerance through Islamic Education: Implementing Moderation Values in the Classroom - Siti Rohmatin Nazilah; Kholilur Rahman; Fathi Hidayah; Imam Wahyono; Hasan Baharun (PALAPA, 2024)
This research focuses on instilling the values ​​of moderation in learning Islamic religious education at school. The study's main aim is to explore how to integrate the values ​​of moderation, contextual learning, character development, and parental and community involvement influences attitudes of tolerance among students. The research method is a descriptive qualitative approach with data collection techniques including in-depth interviews, participatory observation, and document analysis. Data analysis was done through data display, reduction, and conclusion. The research results show that integrating moderation values ​​in learning through contextual methods and character development has increased attitudes toward religious tolerance among students. Parental and community involvement also plays a vital role in supporting the implementation of these values. This research implies that an integrated and collaborative approach to education can strengthen student character and promote religious tolerance. This research contributes to the development of more inclusive and tolerant Islamic education. It underlines the need for further research to accommodate variations in gender, age, and survey methods so that the results obtained can be used on a more appropriate policy basis.